Catalytic processing of the acid tars - Krymets, Grigorii V.; Litynska, Marta I.; Melnychuk, Oleksandr V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2022)
Acid tars are wastes from the processing of coal, petroleum, and petrochemicals (oil refining, benzene refining and petroleum fractions refining and alkylation of isobutane with butenes). Acid tar compositions include resinous substances, organic matter, and polymerization products of unsaturated hydrocarbons. The presence of free sulfuric acid in acid tars often reaches 70 % by weight. Almost all metals from oil are concentrated in tars, and the content of vanadium and nickel can reach 0.046 and 0.014 %, respectively. A lot of countries keep acid tar in the open air in spent quarries, storage ponds, barns, lagoons or near landfills. It poses a risk or even potential threat to people and to the environment nearby due to soil, water, and air pollution. Thus, disposal of the acid tars is a very important ecological and industrial task. In this study, we have researched catalytic cracking and distillation as the utilization methods for acid tar. Anhydrous AlCl3 was used as a catalyst during the cracking of petroleum residues to obtain volatile gasoline fractions due to its catalytic activity in many organic reactions. The catalyst ratios (0.15 g/g of tar or 0.1 g/g of tar) had a very significant influence on the number of volatile fractions and boiling temperature in the acid tar cracking process. According to the results of 1H NMR research, the main components of volatile fractions in the case of catalytic cracking were alkanes CH3-(CH2)n-CH3. The compositions of these fractions were similar to the compositions of gasoline and diesel fuel. A series of distillation experiments (distillation of previously deacidified and centrifuged tar, acid tar without deacidification and centrifugation, and previously deacidified tar without centrifu-gation) gave different results for each type of material. Aliphatic hydrocarbons were the main components of volatile fractions (~ 80, ~ 60 and ~ 90 %, respectively) and the contents of aliphatic S-organic compounds were also significant (~ 10, ~ 30 and ~ 8 %). Thus, both for catalytic cracking and for tar distillation, aliphatic hydrocarbons were the main component of volatile fractions. Deacidification of tar increased the yield of aliphatic hydrocarbons during tar distillation and decreased production of S-organic compounds due to its reactions with calcium carbonate. It is perspective in the context of fuel production.